The Istinbāṭ Mechanism of the Indonesian Ulema Council (MUI) Fatwas in Islamic Family Law - M Salman Alfarisi; Mughniatul Ilma (Universitas Islam Negeri Sumatera Utara, 2026)
The Indonesian Ulama Council (Majelis Ulama Indonesia/MUI) plays a strategic role in responding to contemporary issues of Islamic family law through the issuance of fatwas. This article examines the legal foundations and mechanisms of istinbāṭ al-ḥukm employed by MUI in formulating fatwas related to Islamic family law. This study uses library research with a content analysis approach by examining selected MUI fatwas, including fatwas on interfaith marriage, assisted reproductive technology (in vitro fertilization), and divorce through digital media issued between 2005 and 2020. The findings show that MUI applies a model of collective ijtihād (ijtihād jamā‘ī) that integrates classical Islamic legal sources, such as the Qur’an, Sunnah, consensus, and analogy, with contextual considerations and the objectives of Islamic law (maqāṣid al-sharī‘ah). This approach reflects a contextual-normative legal orientation that maintains textual authority while responding to social changes within Muslim family life in Indonesia. This study contributes to the understanding of institutional fatwa-making in Indonesia and highlights the relevance of MUI fatwas as moral and social references in the development of contemporary Islamic family law.